2014
DOI: 10.4028/www.scientific.net/amm.513-517.28
|View full text |Cite
|
Sign up to set email alerts
|

Helicon Plasma Discharge for Processing Wall Material

Abstract: A helicon wave plasma (HWP) discharge with strong magnetic field was investigated. The HWP was produced with an internal Nagoya III antenna that is perpendicular to the magnetic field and driven by a 13.56 MHz radio-frequency (RF) source. HWP was characterized in terms of electron density, electron temperature and plasma potential using a single Langmuir probe in Ar gas. The result of Langmuir probe shows that the electron density increases with RF power, but saturate above 700 W at a density of 2×1019m-3. Sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…[28][29][30] In HMHX, the magnitude of the magnetic field is controlled by the direct-current (DC) power supply. After calculation, it is found that the magnetic field strength is proportional to the current, and the proportional relationship satisfies the following relationship: [31] B = 1.4814 × 10 −3 I, (B in T, I in A) .…”
Section: Resultsmentioning
confidence: 99%
“…[28][29][30] In HMHX, the magnitude of the magnetic field is controlled by the direct-current (DC) power supply. After calculation, it is found that the magnetic field strength is proportional to the current, and the proportional relationship satisfies the following relationship: [31] B = 1.4814 × 10 −3 I, (B in T, I in A) .…”
Section: Resultsmentioning
confidence: 99%
“…More than half a century after the discovery of helicon waves [139,140], helicon plasma sources remained an important field of study in plasma physics. Their almost unique properties of producing very high plasma density up to 10 13 cm −3 , and electron temperature up to 10 eV [141] favor its application ranging from the study of planetary plasmas, to the recently popular study of wakefield accelerators [74,142] and to material processing applications [143]. Extensive research has been done on the propagation and absorption of helicon wave [144].…”
Section: Helicon Plasma Related Physicsmentioning
confidence: 99%